The apocryphal epistle to the Laodiceans : an epistolary and rhetorical analysis - Tite, Philip L., 1969- (Texts and editions for New Testament study, 2012)
Challenging nearly two centuries of scholarship, The Apocryphal Epistle to the Laodiceans offers the first close analysis of Laodiceans. Philip Tite offers a detailed study of this Latin letter by exploring the epistolary conventions utilized by the letter writer.